Многоканальная измерительная система для калибровки высокотемпературных генераторов шума - Berezhnoi, V. А.; Kuzhel, V. I.; Ostapchuk, A. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The principle of construction and the results of development and research of a multichannel measuring system in the millimeter wavelength range are considered. The system is designed for calibration of high-temperature noise generators in the frequency range of 86–100 GHz.